The influence of tourist infrastructure on the tourist satisfaction in Ohrid - Daliborka Blazeska; Zoran Strezovski; Angela Milenkovska Klimoska (UTMS Journal of Economics, 2018)
The purpose of the paper is to stress the importance of permanent improvement of tourism infrastructure in advancing tourism satisfaction on destination. It is empirical research of influence of tourism infrastructure on destination on tourist satisfaction in Ohrid city in R of Macedonia. Tourism infrastructure is a range of devices and institutions constituting material and organizational basis for tourism development. It comprises four basic elements: accommodation facilities, gastronomy facilities, accompanying facilities and communication facilities. Policies are needed to improve infrastructure, promote the integration of tourist services, maintain visitor numbers and encourage guests to stay longer, visit additional locations and increase their spending. Ohrid city is famous tourist destination in Republic of Macedonia. Despite historical and cultural treasures located in Ohrid, it is most famous for the Ohrid Lake. Th. city has strong attractive factors - natural and cultural monuments that attract tourist. The subject of this paper is the tourism infrastructure in Ohrid city, the current status and perspectives in order to attract more foreign and domestic tourists. Ohrid city in cooperation with government of R. Macedonia should improve permanently tourism infrastructure in destination. This paper presents an action research conducted on a sample of 200 foreign visitors in Ohrid city period of 01 July till 01 august. 2017. Tourist infrastructure has huge influence of tourist satisfaction from destination. Local municipality of Ohrid city with join efforts with the government of Republic of Macedonia should permanently develop tourist infrastructure.
Keywords: M13; Z33; L83; 330; Tourism infrastructure; foreign tourists; tourist satisfaction; Ohrid City